ENHANCEMENT OF THE PERFORMANCE OF A TRANSFER FIELD ELECTRIC MACHINE OPERATING IN THE ASYNCHRONOUS MODE (Nigerian Journal of Technology, 2014)
This paper reports the enhancement of the output power and power factor of a transfer field machine operating in the asynchronous mode by direct capacitance injection into the auxiliary winding of the machine, which is electrically isolated from the main winding but magnetically coupled to it. It is shown that by proper tuning of the injected capacitance, the torque and output power of the machine is markedly enhanced at improved power factor. With the enhanced output power achievable by capacitance injection, the transfer field machine can compare favorably with an equivalent induction motor except that the synchronous speed is inherently limited to half the frequency of the stator mmf wave (?r = ½?o)